Multimodal Analysis: Revealing Bayu Skak’s Frustration in “Valentine Janc#k” Video - Natasya Evelyn Alamsyah (Institute of Research and Community Outreach - Petra Christian University, 2021)
This qualitative study aimed to know the meaning of an expression especially Bayu’s expressions in this “Valentine Janc#k” video. Expression is something that cannot be separated from a conversation. The expression itself has various meanings; sometimes the same expression can have two or even more meanings. To get the accurate meaning, all aspects within us must work together such as: facial expressions, gesture, and also the choice of words used. Just like what the writer found in this